Salivary proteins, proteases, and disease pathophysiology in oral health and precision diagnostics: a narrative review - Viorica Rarinca; Cătălina Ionescu; Malina Visternicu; Alin Ciobica; Ionela Vlasie; Anca Trifan; Vasile Burlui; Ancuta Andreea Miler; Andrei Luca; Otilia Novac; Bogdan Novac (Frontiers in Dental Medicine, 2026)
The oral cavity represents a highly complex biochemical ecosystem in which host tissues, saliva, microbial communities, and environmental factors interact dynamically to maintain health or promote disease. This narrative review examines a comprehensive overview of the biochemical processes occurring within the oral cavity and examines their implications for oral health and disease. Key aspects discussed include the biochemical composition and functions of saliva, the metabolic activity of the oral microbiota, biofilm formation, and the molecular mechanisms underlying major oral diseases such as dental caries, periodontal disease, and oral mucosal disorders. Particular emphasis is placed on the role of biochemical homeostasis, microbial dysbiosis, inflammation, and oxidative stress in disease pathogenesis. Although substantial progress has been made in characterizing these mechanisms, current evidence remains largely derived from in vitro or reductionist models that do not fully replicate the complexity of the oral environment. In addition, inter-individual variability and host-microbial interactions are still incompletely understood, limiting full translational application. This review also discusses the emerging role of salivary biomarkers as non-invasive diagnostic and prognostic tools, as well as potential therapeutic strategies targeting biochemical pathways. By critically integrating current evidence, this work highlights both advances and remaining gaps in oral biochemistry, emphasizing its relevance for the development of more precise preventive, diagnostic, and personalized approaches in oral healthcare.